Dry matter yield and nutritive value of elephantgrass irrigated during the dry season - Cóser, Antônio Carlos; Martins, Carlos Eugênio; Deresz, Fermino; Freitas, Ary Ferreira de; Paciullo, Domingos Sávio Campos; Alencar, Carlos Augusto Brasileiro de; Vítor, Cláudio Manoel Teixeira (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate irrigation strategies on elephantgrass (Pennisetum purpureum) pasture, during the dry season, upon dry matter yield, plant height, ground cover, and forage quality. The experiment was conducted in the county of Coronel Pacheco, Minas Gerais, Brazil, from June/2004 to January/2007. The treatments evaluated were: treatments with irrigation starting on Jul. 15, Aug. 1st, Aug. 15, Sept. 1st, Sept. 15, and Oct. 1st fertilized with 300 kg ha-1 of N per year, and two control treatments (without irrigation) fertilized with 300 and 200 kg ha-1 of N per year. Two harvest methods were used: hand plucking maintaining a forage stubble height of 80–100 cm and cutting at 10 cm above the soil surface. Both dry matter yield and plant height increased with the earliness of irrigation onset. Pastures with irrigation onset in July and August were ready for grazing four to six weeks earlier than those without irrigation. Dry matter yield obtained by cutting was double that obtained by hand plucking. Crude protein content and in vitro dry matter digestibility were higher with hand plucking than by cutting, but neutral detergent fiber contents were similar.